JAKUB S. BENEŠ, Workers and Nationalism: Czech and German Social Democracy in Habsburg Austria, 1890–1918: Oxford 2017, Oxford University Press, 268 s. - Rákosník, Jakub (Dějiny – teorie – kritika, 2019)
Review.